The man who stayed behind - Rittenberg, Sidney 1921-2019; Bennett, Amanda (Duke University Press, 2001)
The story of "an idealistic young American who freely cast his lot with the Chinese revolution only to be struck down by that revolution at the floodtide of its success."--Leonard Woodcock, first American Ambassador to China.
Keywords: Rittenberg, Sidney; Rittenberg, Sidney -- 1921-2019; Geschichte 1949-1976; Geschichte; Communists -- China -- History -- Biography; Autobiografie; USA; China -- History -- 1949-1976; China -- History -- Civil War, 1945-1949; United States -- Biography; China; Biografie